Investigating the Prevalence of Self-Medication with Antibiotics and Related Factors among those who Refer to Health Care Centers in the City of Kerman - Arash Farvahari; Mina Danaei; Ali Sheibani Tezerji; Mohsen Momeni (Tehran University of Medical Sciences, 2023)
Background and Aim: Nowadays, due to people using antibiotics without prescription, the resistance of the bodies to antibiotics has been a major health issue in the world. This study aimed to investigate the consumption of antibiotics without prescription among the people that go to the health care centers of Kerman. Materials and Methods: This descriptive-analytical study was conducted from April to September 2019, cross-sectionally on 331 people who were referred to the health care centers of Kerman city by the available sampling method. In this research, a valid questionnaire was used to collect information. Data was analyzed with SPSS statistical software, using t-test and chi-square statistical tests. Results: The average age of the referred people in this study was 38.6±10.76 years, 135 (40.4%) were males and 194 (60.6%) were females. More than two-thirds of people had a higher education than deploma degrees. The self-medication prevalence with antibiotics was 32.9%. The most common cause of self-inflicted use of antibiotics is unwillingness to pay (34.4%), the most common types of antibiotics used are amoxicillin (25%) and azithromycin (24%), and the most common form of medicine used is pills (55.5%). Respiratory infections were also the most common cause of self-inflicted use of antibiotics (42.2%). Pharmacies were the most common source of information about how to use antibiotics (53.9%). Also, self-medication with antibiotics in married people (P=0.015). people with self employed jobs (P=0.031) and people without medical insurance (P<0.001) were significantly more than the other studied group. Conclusion: The results of the present study showed self-medication with antibiotics is highly prevalent in Kerman city, and policy makers should take interventions to increase people's awareness of the risks and side effects of self-inflicted use of antibiotics, as well as drug resistance created as a result, in order to reduce the self-inflicted use of these drugs.